UPAYA ORANG TUA DALAM MENGANTISIPASI BAHAYA NARKOBA DIKALANGAN REMAJA DESA SALAMBUE KECAMATAN PADANGSIDIMPUAN TENGGARA - Nasution, Nur Cahaya (Palita: Journal of Social Religion Research, 2018)
Salambue Village is a village that is quite vulnerable to drug activities. It is evident that dealers, dealers and drug users are increasing and increasing. This study will explore: 1) The Condition of Adolescents Who Misuse Drugs in Salambue Village, 2) Parents' Efforts to Anticipate Narcotics Hazards among Adolescents in Salambue Village II, 3) Parental Obstacles and Challenges in Anticipating Narcotics Hazards in Salambue Sub-District Youth Adolescents Padangsidimpuan Tenggara. This research is qualitative research using descriptive methods. Data collection is done by observation and interview techniques. The results showed that: 1) The Condition of Adolescents Abusing Narcotics in Salambue Village was very alarming because it resulted in psychiatric disorders (crazy), 2) Parents' efforts to anticipate the danger of narcotics among Salambue Villagers included: continuous parental advice, sending their children to school to Pondok Pesantren, punishments that educate, equip children with religious knowledge, children are preoccupied with positive activities, limit child interaction, spend time with children and create comfort in the household so that children feel at home. 3) Obstacles and Challenges of Parents in Anticipating the Dangers of Narcotics in Adolescents Salambue Village, South Padangsidimpuan Subdistrict, is: limited parental time for children, limited parental knowledge about drugs, and village conditions for drug emergency.